ANALISIS RESILIENSI KARIER PADA SELF-EMPLOYMENT (WIRAUSAHA) - Arezah, Ersaliya; Safitri, Rachmayati Eka (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
Career resilience refers to an individual's ability to persist, adapt, and/or grow in their career despite facing challenges, changing circumstances, and ongoing difficulties over time. In this study, 68 respondents who chose self-employment (entrepreneurship) participated in completing a questionnaire on career resilience. These respondents represented diverse business sectors, including consumer goods, food and beverage, services, manufacturing, retail, and integrated agribusiness. The majority of respondents belonged to the millennial generation. The findings revealed that most entrepreneurs demonstrated a moderate level of career resilience. Additionally, the study identified a significant difference in career resilience levels between men and women. These results contribute to the existing body of knowledge, particularly regarding gender differences in career resilience—a topic that remains relatively underexplored in current research.